(untitled) (Research, Society and Development, 2022)
Objective: to identify the prevalence of cesarean sections in Brazil and their distribution in the country according to the maternal socioeconomic and obstetric profile. Methods: ecological study on the prevalence of cesarean sections in Brazil in the period between 2000 to 2019. Bivariate analysis was used to evaluate the spatial autocorrelation between the outcome and the independent variables, generating the Local Moran Index and spatial correlation maps. GeoDa 1.18 was the program used. Results: 59,291,381 live births were registered and the prevalence of cesarean section was 49%. Performing a cesarean section showed overall positive spatial autocorrelation (I= 0.435 p= 0.004) and formation of a High/High cluster for all variables studied in the states of the South, Southeast and Center-West regions. Conclusion: there is a pattern of spatial dependence in the distribution of the prevalence of cesarean sections. It is evident the importance of awareness about the route of delivery, both for pregnant women and health professionals.